The Atacama Cosmology Telescope: ACT-CL J0102-4915 "El Gordo," a Massive Merging Cluster at Redshift 0.87 - Menanteau, F; Hughes, J; Sifon, C; Hilton, M; Gonzalez, J; Infante, L; Barrientos, L; Baker, A; Bond, JR; Das, S; Devlin, M; Dunkley, J; et al. (2011)
We present a detailed analysis from new multi-wavelength observations of the exceptional galaxy cluster ACT-CL J0102-4915 "El Gordo," likely the most massive, hottest, most X-ray luminous and brightest Sunyaev-Zeldovich (SZ) effect cluster known at z>0.6. The Atacama Cosmology Telescope collaboration discovered El Gordo as the most significant SZ decrement in a sky survey area of 755 deg^2. Our VLT/FORS2 spectra of 89 member galaxies yield a cluster redshift, z=0.870, and velocity dispersion, s=1321+/-106 km/s. Our Chandra observations reveal a hot and X-ray luminous system with an integrated temperature of Tx=14.5+/-1.0 keV and 0.5-2.0 keV band luminosity of Lx=(2.19+/-0.11)x10^45 h70^-2 erg/s. We obtain several statistically consistent cluster mass estimates; using mass scaling relations with velocity dispersion, X-ray Yx, and integrated SZ, we estimate a cluster mass of M200a=(2.16+/-0.32)x10^15 M_sun/h70. The Chandra and VLT/FORS2 optical data also reveal that El Gordo is undergoing a major merger between components with a mass ratio of approximately 2 to 1. The X-ray data show significant temperature variations from a low of 6.6+/-0.7 keV at the merging low-entropy, high-metallicity, cool core to a high of 22+/-6 keV. We also see a wake in the X-ray surface brightness caused by the passage of one cluster through the other. Archival radio data at 843 MHz reveal diffuse radio emission that, if associated with the cluster, indicates the presence of an intense double radio relic, hosted by the highest redshift cluster yet. El Gordo is possibly a high-redshift analog of the famous Bullet Cluster. Such a massive cluster at this redshift is rare, although consistent with the standard L-CDM cosmology in the lower part of its allowed mass range. Massive, high-redshift mergers like El Gordo are unlikely to be reproduced in the current generation of numerical N-body cosmological simulations.